Silica-based monolithic capillary columns modified by liposomes for characterization of analyte-liposome interactions by capillary liquid chromatography - Moravcová, Dana; Planeta, Josef; Wiedmer, Susanne K (Journal of chromatography. A, Including electrophoresis and other separation methods, 2013)
This study introduces a silica-based monolith in a capillary format (0.1 mm × 100 mm) as a support for immobilization of liposomes and its characterization in immobilized liposome chromatography. Silica-based monolithic capillary columns prepared by acidic hydrolysis of tetramethoxysilane in the presence of polyethylene glycol and urea were modified by (3-aminopropyl)trimethoxysilane, whereby amino groups were introduced to the monolithic surface. These groups undergo reaction with glutaraldehyde to form an iminoaldehyde, allowing covalent binding of pre-formed liposomes containing primary amino groups. Two types of phospholipid vesicles were used for column modification; these were 2-oleoyl-1-palmitoyl-sn-glycero-3-phosphatidyl choline with and without 1,2-diacyl-sn-glycero-3-phospho-L-serine. The prepared columns were evaluated under isocratic separation conditions employing 20mM phosphate buffer at pH 7.4 as a mobile phase and a set of unrelated drugs as model analytes. The liposome layer on the synthesized columns significantly changed the column selectivity compared to the aminopropylsilylated monolithic stationary phase. Monolithic columns modified by liposomes were stable under the separation conditions, which proved the applicability of the suggested preparation procedure for the synthesis of capillary columns dedicated to study analyte-liposome interactions. The column efficiency originating from the silica monolith was preserved and reached, e.g., more than 120,000 theoretical plates/m for caffeine as a solute.
Keywords: liposomy; oxid křemičitý; Chromatography, Liquid; léčivé přípravky; sloučeniny síry; Silicon Dioxide; Pharmaceutical Preparations; Sulfur Compounds; Liposomes; chromatografie kapalinová